A novel deletion partly removing the AVP gene causes autosomal recessive inheritance of early‐onset neurohypophyseal diabetes insipidus. (17th January 2012) - Christensen, JH; Kvistgaard, H; Knudsen, J; Shaikh, G; Tolmie, J; Cooke, S; Pedersen, S; Corydon, TJ; Gregersen, N; Rittig, S
<x xml:space="preserve">Abstract</x> Christensen JH, Kvistgaard H, Knudsen J, Shaikh G, Tolmie J, Cooke S, Pedersen S, Corydon TJ, Gregersen N, Rittig S. A novel deletion partly removing the AVP gene causes autosomal recessive inheritance of early‐onset neurohypophyseal diabetes insipidus. Familial neurohypophyseal diabetes insipidus (FNDI) typically presents with age‐dependent penetrance and autosomal dominant inheritance caused by missense variations in one allele of the AVP gene encoding the arginine vasopressin (AVP) prohormone. We present the molecular genetic characteristics underlying an unusual form of FNDI occurring with very early onset and seemingly autosomal recessive inheritance. By DNA amplification and sequencing, we identified a novel variant allele of the AVP gene carrying a 10, 396 base pair deletion involving the majority of the AVP gene as well as its regulatory sequences in the intergenic region between the AVP and the OXT gene, encoding the oxytocin prohormone. We found two chromosomes carrying the deletion in affected family members and one in unaffected family members suspected to transmit the deleted allele. Whole‐genome array analysis confirmed the results and excluded the presence of any additional major pathogenic abnormalities. The deletion is predicted to abolish the transcription of the AVP gene, thus the fact that family members heterozygous for the deletion remain healthy argues, in general, against haploinsufficiency as the pathogenic mechanism FNDI. Accordingly, our data is strong support to the prevailing idea that dominant inheritance of FNDI is due to a dominant‐negative effect exerted by variant AVP prohormone.